THE GLOBAL ENVIRONMENTAL PROBLEM OF GARBAGE AND WAYS TO SOLVE IT - Shermatova Zamira Sherzod kizi , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Garbage pollution is one of the main environmental problems of our time. Every year the Earth is increasingly covered with waste, and large areas are allocated to landfills. That is why recently scientists around the world have been looking for effective ways to recycle waste.